A History of Religious Broadcasting in Korea from a Religious Politics Standpoint: Focusing on the Period of a Protestant Broadcasting Monopoly - Lee, Sungmin (Journal of Korean religions, 2017)
The objective of this paper is to reveal the context of the "politics of religion" to better understand the place of religious programming in Korea's broadcasting history through an examination of the history of Protestant broadcasting in South Korea. Historically, religious broadcasters have been influential in Korea, not in the limited sphere of any specific religion, but in their close ties with the forces of social change. Religious broadcasting in South Korea was initiated because of the unique characteristics of the First Republic and its self-image as a "quasi-Christendom." In the context of the need for South Korea's military regimes to manage religions by treating them differentially, religious broadcasting experienced a variety of twists and turns, including its marginalization into "special broadcasting," and its evolution into a social institution for critical journalism. This paper offers a different perspective on the public interest when associated with "religious broadcasting."